Management of type I gastric-neuroendocrine tumors: the less the better? - Rossi, Roberta Elisa; Masoni, Benedetta; Poletti, Valeria; Maselli, Roberta; Carrara, Silvia; Bertuzzi, Alexia Francesca; Uccella, Silvia; Lania, Andrea Gerardo Antonio; Zerbi, Alessandro; Hassan, Cesare; Repici, Alessandro (Frontiers in Endocrinology, 2025)
Background and aimsType I gastric neuroendocrine tumors (gNETs) are known for their favorable prognosis. We aimed to present a real-life experience at a tertiary referral center.Materials and methodsRetrospective analysis of patients diagnosed with type I gNETs at our Institution between 2014 and 2024.ResultsA total of 36 lesions were identified in 23 patients, with a median tumor size of 7 mm (range 2-20 mm). There were 29 out of 36 lesions that were G1, and 7 were G2. In 13 cases, endoscopic ultrasound (EUS) was performed prior to resection, revealing lymph node involvement in one 20-mm G1 lesion that required surgery. A 15-mm G2 lesion underwent surgery. In the remaining 34 lesions, endoscopic resection was performed: forceps in 5, cold-snare polypectomy in 4, hot-EMR in 22, EMR-cap in 1, ESD in 1, hybrid-ESD in 1. Among those, one 5-mm G2 lesion, previously removed via simple polypectomy, required surgery due to the 14.5% Ki-67 index. The median follow-up was 14 months (range 1-120), with 10 cases of local recurrence in 6 patients, median tumor size 3 mm (range 2-8 mm), all G1. In three cases, endoscopic surveillance was indicated; seven NETs underwent endoscopic resection (three forceps, two EMR-cap, two EMR), with EUS being performed in four cases with negative results. No local/distant metastases nor tumor-related deaths occurred.ConclusionsPresent data confirm an indolent behavior for type I gNETs. Preoperative EUS staging led to a change in the management in one case, which highlights the need of dedicated studies to identify predictive factors to stratify risk and plan the management of these neoplasms.